(untitled) (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2020)
The 2030 Agenda for Sustainable Development adumbrated the goals for sustainability that United Nations Member-states in 2015 pledged to pursue. Of the 17 Global Goals, quality education is one of them, which is also known as Goal 4 of the 2020 United Nations Development Programme. The adoption of the multigrade teaching approach, wherein a teacher in his tutelage integrates learners from two or more grade levels, responds to EFA goals. This condition inspired the conduct of this study to ascertain the effectiveness of integrated multigrade Mathematics instruction in achieving a higher level of Mathematics competence. The one-grouped pre-test and post-test design. Before the conduct of the experiment, the researcher adhered to the research ethics protocol of the College by seeking permission from the authorities before conducting the study. Consequently, the pupils underwent intervention activities using the researcher-designed learning plan integrating the Mathematics competencies for Grades 1 and 2. The data gathered was treated using descriptive and inferential statistics. The findings showed that pupils in both grade levels registered a fairly satisfactory Mathematics performance; nevertheless, they registered increased scores from the pre-test to the post-test. Moreover, the test of difference showed a significant difference in the respondents’ mathematics performance, leading the researcher to reject the null hypothesis and accepted the alternative hypothesis that there was indeed a significant difference in the respondents’ mathematics performance before and after the intervention activity. The above findings illustrated the positive impact of using the intervention material in developing the mathematics competencies of Grade 1 and 2 in a multigrade classroom. Thus, the integrated learning plan for IPEd multigrade mathematics classrooms helped improve the performance of the learners. With this, the researcher strongly recommended the adoption of the multigrade Mathematics IPED learning plan.